A Study on Gender Disparity in Agricultural Resource Management in the State of Uttarakhand, India - , Pratibha Pandey; , Deepa Vinay; , Seema Kwatra; , S. B. Singh; , Govind Singh Kushwaha (Archives of Current Research International, 2024)
Agriculture is one of the drudgery-prone jobs in the unorganized sector, which employs the majority of women. Since agriculture provides them with bread and butter, many Uttarakhand hill people still make agriculture their primary source of income. Planting, transplanting, weeding, thinning, harvesting, winnowing, processing, selling, storing, taking care of animals, kitchen gardening, and other chores are just a few of the numerous jobs that women perform in the agricultural industry. The current study aims to evaluate the disparity between genders in the agriculture sector's resource access. The study was conducted in two districts of Uttarakhand, AER 9 (Udham Singh Nagar) and AER 14 (Almora). The study area and samples were chosen using a combination of random selection and the purposeful sampling technique. The data was collected between August 2023 and February 2024. There were 240 samples in all. Data was collected for the selected samples through survey method. Appropriate statistics such as frequency, percentage, etc. were used to analyse the data in Microsoft Excel. With 80.33–98.33% of respondents having minor agricultural implements, the bulk of respondents have over 15 years of farming experience. When it comes to labour and marketing, men rule, although women are more likely to help with weeding and produce sorting/storage. Very few households own large farm implements. Men handle land-related chores and chemicals, equipment, and fertilizers, whereas women are more likely to work on off-farm tasks like gathering firewood and fetching water. The findings demonstrated that men generally hold more powerful positions and have access to and control over significant farm resources, particularly when it comes to crucial decision-making areas like land transactions and the purchase of tools and implements. The percentages for female and joint control indicated regions that might be targeted for the promotion of equal access to and control over agricultural resources through gender-inclusive policies and actions.